Molecular Actions of Thyroid Hormone on Breast Cancer Cell Migration and Invasion via Cortactin/N-WASP - Uzair, Ivonne Denise; Conte Grand, Jeremias; Flamini, Marina Ines; Sanchez, Angel Matias (Frontiers in Endocrinology, 2019)
The thyroid hormone triiodothyronine (T3) plays a fundamental role in growth regulation, differentiation, metabolism and cellular movement. These processes are particularly important considering that deregulation of T3 levels could promote abnormal responsiveness of mammary epithelial cells, which may lead to the development and progression of breast cancer (BC). Once cells migrate and invade different tissues, BC metastasis is the main cause of cancer-related death because it is particularly difficult to revert this multistep process. Cell migration integrates several steps that induce changes in cell structure and morphology to promote BC cell invasion. These sequential steps include actin cytoskeleton remodeling, focal adhesion complex formation and, finally, the turnover of branched actin filament networks. In this article, we demonstrate that T3 has the ability to modify the Epithelial-Mesenchymal Transition process. In addition, we show that T3 induces actin cytoskeleton reorganization, triggers focal adhesion formation and, as a consequence, promotes actin nucleation via non-genomic pathway. These events are specifically modulated by T3 via integrin αvβ3 to FAK/paxillin/cortactin/N-WASP/Arp2/3 complex signaling pathway, increasing cell adhesion, migration and invasion of T-47D BC cells. We suggest that T3 influences the progression of tumor metastasis by controlling signaling pathways that converge in cell motility. This knowledge is crucial for the development of novel therapeutic strategies for BC treatment.